Adopsi Technology Continuance Theory, Extend Technology Proficiency, dan Social Influence untuk menganalisis Continuance Intention pada Aplikasi Travel - Putra, M. Naufal Rizqullah Kesih S.; A., Faris Muslihul; Amrozi, Yusuf; Ilham, Ilham; Ananto, Prasasti Karunia Farista (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
A travel application is an application that allows tourists to manage various travel-related activities, such as searching for flights, accommodation, tourist activities, and booking flights at any time just by using a mobile device. This research applies the concept of Technology Continuance Theory (TCT) discovered by Liao et al., (2009), and deepens it with Technology Proficiency and Social Influence to identify what factors influence Continuance Intention in using travel applications. This research used a quantitative approach with 120 respondents using Agoda, Tiket.com, and Traveloka. The questionnaire was prepared using a Likert scale which identified 14 hypotheses. SEMP-PLS was applied for data analysis using SmartPLS v.3 software and provided results from 14 proposed hypotheses, it was discovered that 5 of them did not support this research. Satisfaction, Attitude, and Social Influence were proven to directly influence Continuance Intention, while Perceived Usefulness was found to have no significant influence. The addition of Technology Proficiency has a strong influence on Continuance Intention, and Social Influence was found to influence Continuance Intention through the mediator variable, is Satisfaction.